Effects of Construction Grammar-based Instruction on Unlearning Topic-prominence of Korean EFL Learners’ Interlanguage - Saehee Hwang (Korean Journal of English Language and Linguistics, 2019)
This study investigates effects of two instructional methods, i) Construction Grammar(CxG)-based instruction and ii) instruction on the ungrammaticality of null arguments in English, in removing topic prominence in Korean EFL learners’ interlanguage. Sixty one college students were divided into two experimental groups and the control group, and they were given a four-week instruction. All three groups took a pretest, an immediate posttest, and a delayed posttest of the same grammaticality judgment task which was designed to measure the learners’ acceptance of topic prominent properties. The results showed that explicit teaching on null arguments was effective only in helping the learners better reject the incorrect null subject sentences in the immediate posttest but such effect was not maintained in the delayed posttest. However, the teaching was not effective in making them recognize the ungrammaticality of null object sentences or other topic-prominent sentences. As for the construction-based instruction, there was no significant improvement found in the learners’ performance except for topicalization. In other words, neither the positive evidence focusing on the target language nor the negative evidence on null arguments contributed to the unlearning of topic prominence transferred from L1. KCI Citation Count: 0